Implementing STEAM in the Early Childhood Classroom - Nancy K. DeJarnette (Lectito Journals, 2018)
STEAM (Science, Technology, Engineering, Art, and Math) education has received growing attention over the past decade, primarily within the middle and high school levels. This article focuses on the need for STEAM education at the early childhood level. Preschool children have a natural disposition toward science with their sense of curiosity and creativity. This ethnographic research involved professional development for 50 in-service preschool teachers in an urban high-needs area of the northeastern United States. The researcher explored how providing hands-on professional development, consistent support, and rich resources for STEAM lesson implementation into the early childhood curriculum would impact the dispositions, self-efficacy, and rate of implementation for teachers. The study also involved observation of the reception of STEAM instruction by preschool children. Data was collected through pre and post surveys, teacher interviews, and field observations. Findings revealed an increase in positive dispositions and self-efficacy of preschool teachers, however, the rate of implementation of STEAM lessons by the teachers was initially limited. The reception of the STEAM lessons by these high-needs preschool children was phenomenal with high levels of engagement and cooperation. More research needs to be done in the area of STEAM implementation in the PK-12 classrooms to incorporate engineering education.